Study on the efficiency of advanced pressing in the Premier League - Brîndescu, S.; Datcu, F.-R.; Buda, I.-A. (Baltic Journal of Health and Physical Activity, 2021)
Background: Advanced pressing is a tactical relationship which consists of a joint effort which players undertake to win back possession as high up the pitch as possible. It comes as a direct counter to slow build-up styles like the tiki-taka and has existed, historically, for decades. The best examples from history can be Ajax and Feyenoord in the 1970s, as well as the Dutch national team from the same period. In these days, some of English teams use this tactical relationship with the desire to recover the ball as quickly as possible. Material and Methods: In order to analyze the efficiency of advanced pressing in modern football, we have used statistical analysis which we took from the site fbref.com [accessed on 20 April, 2021], key raw pressing statistics like % of successful pressing attempts, as well as viewing football games to see which teams use a high, medium or low defensive block. We have analyzed how far up the pitch they usually defend and press, how successful they are with their pressing and what their dependencies are. Results: On average, although there is a dependency on the quality of the players available in the squad, teams which adopted an advanced pressing tactic had better results than teams which did not. They won the ball higher up the field and initiated goal actions much closer to the opposition`s goal. Conclusions: In modern football, teams which use advanced pressing have better results than teams who prefer to sit deep and let the opposition build from the back. Advanced pressing produces good results for other attacking statistics as well: entries in the final third, expected goals and overall league position, but it is not the only success factor. Teams still need to be capable of holding their defensive shape in order to avoid having large gaps between their defenders and their attackers.